2016
DOI: 10.1371/journal.pone.0160261
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Correlate with Disability and Disease Course in Multiple Sclerosis Patients: An Italian Multi-Center Study Using the Beck Depression Inventory

Abstract: BackgroundDepression occurs in about 50% of patients with multiple sclerosis. The aims of this study was to investigate the prevalence of depressive symptoms in a multicenter MS population using the Beck Depression Inventory II (BDI II) and to identify possible correlations between the BDI II score and demographic and clinical variables.MethodsData were collected in a multi-center, cross-sectional study over a period of six months in six MS centers in Italy using BDI II.Results1,011 MS patients participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 42 publications
1
29
1
Order By: Relevance
“…Similar frequencies of depression have been found early after symptom onset: in an Australian multicentre cohort of people recruited soon after symptom onset (n = 236), the frequency of positive depressionscreen as measured by HADS was 16.0% (Simpson et al, 2016), greater disability associated with positive depression-screen. Studies of depression in MS using other depression screening tools have found similar results (Brown et al, 2009;Chwastiak et al, 2002;Solaro et al, 2016), with fatigue the most consistent determinant.…”
Section: Introductionmentioning
confidence: 62%
“…Similar frequencies of depression have been found early after symptom onset: in an Australian multicentre cohort of people recruited soon after symptom onset (n = 236), the frequency of positive depressionscreen as measured by HADS was 16.0% (Simpson et al, 2016), greater disability associated with positive depression-screen. Studies of depression in MS using other depression screening tools have found similar results (Brown et al, 2009;Chwastiak et al, 2002;Solaro et al, 2016), with fatigue the most consistent determinant.…”
Section: Introductionmentioning
confidence: 62%
“…However, BDI was used widely in the selection of depressive symptoms in different groups of patients such as: psoriatic patients [30], multiple sclerosis [31,32], adolescents from dysfunctional families [33], high school adolescents [34], patients with dry eyes disease [35], in medical students [36], patients with coronary disease [37], patients with rheumatoid arthritis [38] etc.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent among diagnostic instruments is the long‐standing Beck Depression Inventory (BDI/BDI II; Beck, Ward, Mendelson, Mock, & Erbaugh, ; Beck & Steer, ) , and the more recent Beck Anxiety Inventory (BAI; Beck, Epstein, Brown, & Steer, ). Copious research evidence supports the view that both the BDI and BAI have robust utility in identifying patients with clinically significant anxiety and/or depression symptomatology in primary and acute care settings (Brown, Schulberg, & Madonia, ; Clark et al., ; Furlanetto, Mendlowicz, & Bueno, ; Gatchel & Schultz, ; Green, Brown, Jager‐Hyman, Steer, & Beck, ; Holtzheimer et al., ; Johnson, Neal, Brems, & Fisher, ; Lykouras et al., ; Manne et al., ; Novy, Nelson, Berry, & Averill, ; Piotrowski & Lubin, ; Reeves, Rohan, Langenberg, Snitker, & Postolache, ; Schneibel et al., ; Solaro et al., ; Strik, Honig, Lousberg, & Denollet, ; Wu, ). Yet, critiques claim that the Beck Inventories are “behavior‐based”, and thus, neglect the important domain areas such as cognitive and emotional factors (see Eack, Singer, & Greeno, ).…”
Section: Current Studymentioning
confidence: 93%